Oncogenic v-Abl tyrosine kinase can inhibit or stimulate growth, depending on the cell context. - Renshaw, M W (1992)
The v-abl oncogene of Abelson murine leukemia virus (A-MuLV) induces two opposite phenotypes in NIH3T3 cells. In the majority of cells, v-abl causes a growth arrest at the G1 phase of the cell cycle; while in a minority of cells, v-abl abrogates the requirement for growth factors. Using temperature sensitive mutants, it can be demonstrated that v-Abl tyrosine kinase is required for growth inhibition or stimulation. The two phenotypes are not caused by mutations or differences in the expression of v-Abl, but are dependent on the cell context. Two stable subclones of NIH3T3 cells have been isolated that exhibit similar morphology and growth characteristics. However, upon infection with A-MuLV, the 'positive' cells become serum- and anchorage-independent, whereas the 'negative' cells become arrested in G1. The positive phenotype is dominant, shown by cell fusion, and treatment with 5-azacytidine converts the negative cells to the positive phenotype. Activation of v-Abl tyrosine kinase induces the serum-responsive genes in the positive but not in the negative cells. Transactivation of the c-fos promoter by v-Abl in transient assays is also restricted to the positive cells. These results show that v-Abl tyrosine kinase is not an obligatory activator of growth, but requires a permissive cellular context to manifest its mitogenic function.